FIRMS LEVERAGING SUSTAINABILITY-DRIVEN CHANGE: EVIDENCE FROM A SECOND-TIER REGION IN MEXICO - Lopez Castellanos, Fatima (2022)
This thesis explores and investigates how companies located in a second-tier region of an emerging economy have benefited from the adoption of corporate sustainability (CS) programmes. Considering that these companies are immersed in tougher day-to-day problems and struggles than those located in developed countries, it would not be surprising that sustainability compliance is seen as another issue to deal with. Hence the importance of better understanding and providing them with tools that would enable a sounder contribution to sustainable development.